HUBUNGAN MODAL PSIKOLOGIS DAN KOMITMEN ORGANISASIONAL GURU SMA NEGERI DI KABUPATEN PATI - Dwi Julyati Kustinah, 12.52.02.0033; Fauzan, Muhamad (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study is to determine the relationship between psychological capital on teacherâs organizational commitment on state high school at Pati regency. The population in this study are all teachers who are civil servants at state high schools in Pati regency as many as 336 people. The samples in this study are drawn proportional random sampling with 183 respondents. While this study data analysis techniques using multiple regression analysis technique The results show that: 1) there is a strong and significant relationship between optimism, hope and resilience with affective commitment, 2) there is a strong and significant relationship between optimism, hope and resilience with continuance commitment, 3) there is a strong and significant relationship between optimism, hope and resilience with normative commitment. The conclusion of this study is to build a professional teacher, in addition to competence capital, social capital needs to be considered psychological capital held by teachers that if a teacher is a strong psychological capital will be the stronger their commitment to remain and the stronger their involvement in the organizationKeywords: optimism, hope, resilience, affective commitment,Â continuance commitment and normative commitment